(In)effective Thesis Writing and Supervision: (Lost) Opportunity for Learning - Bastola, Madhu Neupane; Bhandari, Bal Mukunda (Studies in ELT and Applied Linguistics, 2021)
Correction: The first author's name was mis-spelt on the webpage. On 18th November 2021, 'Bastika' was changed to 'Bastola'. The PDF remains correct. Thesis writing requires a wide range of reading, the skill of critiquing, a good skill of academic writing, and a proper collaboration of student and supervisor; however, it is poorly understood, less explored, and replete with problems. In this paper, we present the merits of thesis writing, supervisors' and students' commonly held perceptions, the effectiveness of supervisory feedback, and the value of student engagement. Then we present two components of thesis writing (i.e., introduction and literature review, including theoretical framework). Considering the need of the novice researchers (i.e., master's students) who are writing their thesis for the first time, we present these two components' introduction and provide suggestions for supervisors. We also present commonly used language features and examples. This paper is expected to be beneficial to students and supervisors alike.